A critical review of Irrigation-as-a-Service (IAS) models in Ghana: current practices, opportunities, and challenges - Agyemang, Daniel; Tilahun, Seifu A.; Atampugre, Gerald; Ofosu, Abena; Minh, Thai Thi (International Water Management Institute, 2025)
Ghana’s irrigation sector is at a pivotal juncture, transitioning from traditional, donor-driven models toward decentralized, farmer-led, and market-based systems. With increasing climate variability, rising water demand, and growing feasibility of solar-powered irrigation systems (SPIS), the country has an opportunity to redefine its approach to agricultural water management. SPIS presents a sustainable pathway to enhance productivity, climate resilience, and income diversification, particularly for cocoa and vegetable farmers. However, adoption remains limited by high upfront costs, weak extension support, fragmented supply chains, and inadequate institutional and policy coordination. To overcome these challenges, three differentiated scaling pathways are proposed, aligned with the diverse resource capacities of Ghanaian farmers. Resource-rich farmers, typically owning medium to large plots and with access to credit, are best suited for ownership models, allowing them to invest directly in SPIS and potentially offer irrigation services to neighboring smallholders. Resource-limited farmers, cultivating smaller plots with irregular cash flows, would benefit from cooperative or shared ownership models, such as Pay-As-You-Go (PAYG) or seasonal leasing schemes that distribute costs and risks among groups. Resource-poor farmers, often land-insecure or marginalized, require fully serviced irrigation-as-a-service (IAS) models, where third-party providers own and operate systems, offering irrigation through contract-based or on-demand services. Scaling these pathways will require coordinated public–private partnerships, innovative financing mechanisms, capacity development, and policy alignment. Integrating SPIS into national programs such as Planting for Food and Jobs and Climate-Smart Cocoa will help mainstream adoption, while digital tools and blended finance can enhance affordability and efficiency. By tailoring business and service delivery models to farmer realities, Ghana can unlock the transformative potential of solar-powered irrigation advancing climate-smart agriculture, improving water and energy efficiency, and fostering inclusive, sustainable rural livelihoods.